MENTORING: A REVIEW OF EARLY CAREER RESEARCHER STUDIES - Boeren, Ellen; Lokhtina-Antoniou, Irina; Sakurai, Yusuke; Herman, Chaya; McAlpine, Lynn (Frontline Learning Research, 2015)
This paper reviews 23 journal articles on ‘mentoring’ in the context of Early Career Researchers, defined as those in academia with less than 10 years of experience from the start of their PhD. Achieving a better understanding of mentoring is important since within the higher education context new dynamics have created expectations towards more supportive mechamisms for ECRs.<!--?xml:namespace prefix = "o" ns = "urn:schemas-microsoft-com:office:office" /--> In order to better understand the benefits of mentoring for ECRs careers and psychosocial well-being, it is important to understand (1) the core definitions of mentoring used in research, (2) the research methodologies that are applied to research mentoring, (3) the empirical evidence showing the value of mentoring and (4) the remaining gaps for which future research will be needed. Results of the review lead to the following conclusions: there is much research to do, first, to better inform our conceptualization of ECR mentoring and, second, to better understand the value of ECR mentoring support. A research agenda is outlined.